Physiological and molecular sex differences in human skeletal muscle in response to exercise training. (7th December 2021) - Landen, Shanie; Hiam, Danielle; Voisin, Sarah; Jacques, Macsue; Lamon, Séverine; Eynon, Nir
Abstract: Sex differences in exercise physiology, such as substrate metabolism and skeletal muscle fatigability, stem from inherent biological factors, including endogenous hormones and genetics. Studies investigating exercise physiology frequently include only males or do not take sex differences into consideration. Although there is still an underrepresentation of female participants in exercise research, existing studies have identified sex differences in physiological and molecular responses to exercise training. The observed sex differences in exercise physiology are underpinned by the sex chromosome complement, sex hormones and, on a molecular level, the epigenome and transcriptome. Future research in the field should aim to include both sexes, control for menstrual cycle factors, conduct large‐scale and ethnically diverse studies, conduct meta‐analyses to consolidate findings from various studies, leverage unique cohorts (such as post‐menopausal, transgender, and those with sex chromosome abnormalities), as well as integrate tissue and cell‐specific ‐omics data. This knowledge is essential for developing deeper insight into sex‐specific physiological responses to exercise training, thus directing future exercise physiology studies and practical application. Abstract : Abstract figure legend Schematic of sex differences in exercise physiology and their underlying molecular factors. Females exhibit enhanced fatigue‐resistance while males have enhanced muscular strength; females tend to have higher proportions of type I fibres, and tend to oxidize lipids more than carbohydrates during endurance exercise; skeletal muscle transcriptomes differ at baseline and in response to training between the sexes, which likely lead to proteomic sex differences; all of the discussed sex differences arise from a combination of inherent factors such as differences in sex hormone exposure, sex chromosome complement and epigenetic programming (such as DNA methylation (Me) and transcription factors (TF)).